Transformers Rescue Bots. [videorecording (DVD)] Bots' battle for justice. - Burton, LeVar; Chabert, Lacey, 1982-; Blum, Steve, 1965- (Shout! Factory, 2016)
The Rescue Bots are kept very busy protecting Griffin Rock. Join them in five exciting adventures as they work together to keep the peace. Cody and the Bots rescue a stray dog, a mysterious superhero watches over Griffith Rock, the team must defeat an evil villain with plans of destroying the island, and more, as the Bots battle for justice!